Alveolar macrophages in allergic asthma: An expression signature characterized by heat shock protein pathways - Madore, Anne-Marie (Hum Immunol, 2010)
The implication of alveolar macrophages (AM) in asthma, a T(h)2 disease, has not been well characterized. Thus, the goal of this study is to better characterize AM phenotype of allergic asthmatic compared with normal subjects using genomic expression analyses. Microarray analyses were performed with AM isolated from bronchoalveolar lavage. Robust multiarray analysis (RMA) normalization and Smyth's moderated t test were used to select differentially expressed genes. Fifty differentially expressed genes were identified. Nineteen have been classified in categories linked to stress or immune responses and among them; nine are part of the heat shock protein (HSP) family. Difference of expression for three (HSPD1, PRNP, SERPINH1) of the five selected genes were validated using real-time reverse transcription–polymerase chain reaction. Enzyme-linked immunosorbent assay was used to measure the protein level of heat shock protein 60 (HSP60), the protein encoded by HSPD1, and showed difference in AM protein level between allergic asthmatic and control subjects. In summary, this study suggests that HSP gene family, particularly HSP60, is involved in AM functions in a context of allergic asthma. These results also support the involvement of AM immune functions in the development of an allergic asthmatic response.